Use of shell ash from Musa paradisiacal variety Valery as a basic heteroge-neous catalyst in obtaining biodiesel (SCIÉNDO INGENIUM, 2021)
The purpose of the present investigation was to use the peel ash of mature Musa x paradisiaca L (plantain) of the variety "valery" as a basic heterogeneous catalyst in the transesterification reaction. The banana peel was dried at a temperature of 80 ° C for 48 hours and then calcined at 700 ° C for 4 hours. In the calcined banana peel ash (CCPC) their potassium (K) content was determined by the colorimetric method, calcium (Ca) by the volumetric method and its basic strength using the Hammett method. Due to the humidity (0.42%) and acidity index (0.27%) of the used vegetable oil, a direct alkaline transesterification was carried out to obtain biodiesel. The highest yield in biodiesel was 86.94% with 2% with respect to the weight of the catalyst (CCPC), methanol / oil molar ratio 6/1, reaction time, 60 minutes. The results of Potassium 515 mg K / Kg and the basic force 9.8
Keywords: Biodiesel; transterification; banana peel; catalyst